ANALISIS PENYELESAIAN KERUGIAN DAERAH YANG DISEBABKAN OLEH PIHAK KETIGA DALAM PENGADAAN BARANG/JASA PEMERINTAH - Bayu Jaya Kusuma (Master in Accounting Program, 2018)
ABSTRACT Based on the Semester Examination Index (IHPS) I 2017 issued by the Supreme Audit Board (BPK), it is known that the level of regional loss settlement caused by third parties is still low, at 12.89%. In addition, the procedures for resolving state/regional losses caused by third parties are not clearly regulated in the legislation, thus giving rise to differences in the settlement process for various regional governments. This study aims to identify factors that influence the level of regional loss settlement to third parties and provide recommendations on procedures that can be done to ensure the settlement of regional losses caused by third parties.This research was carried out on 2 regional governments that have the highest level of regional losses settlement and 2 local governments with the lowest level of regional losses settlement in the Java and Bali area. This study uses qualitative methods with data collection techniques through written interviews and telephone interviews with officials and staff of the regional government inspectorates under study. In addition, this study also uses document analysis such as regional loss monitoring reports and audit reports published by the BPK.The results of the study indicate that the level of regional loss settlement against third parties is influenced by the commitment of the regional government, audit procedures, third party cooperation, and the constraints faced by local governments in resolving regional losses. The settlement of regional losses to third parties can be done in several ways, namely by deliberation for consensus, arbitration and alternative dispute resolution, as well as litigation through civil lawsuits in court.